Confined jet impingement boiling in a chamber with staggered pillars - Qiu, Lu (2020)
The jet impingement boiling heat transfer is investigated experimentally and numerically in a cylindrical chamber with the dense circular pillars, which is a simplified model of the shell-side chamber of the phase-change heat exchanger in a thermoacoustic Stirling engine. The saturated or subcooled liquid water is impinged onto the horizontal pillars from the bottom inlet of the boiling chamber, whereas the two-phase flow is exhausted through the outlet on the top of the chamber. Aside from the measurements of the wall heat flux and wall temperature, the boiling induced bubbly flow patterns are optically observed with a high-speed camera through the transparent window. In the simulation, the boiling heat transfer is predicted with Rensselaer Polytechnic Institute (RPI) boiling model, in which the wall heat flux is composed of three parts. The predicted boiling curve is compared with the measured one, and the calculated distributions of the vapor volume fraction adjacent to the boiling wall are compared with the captured images. The reasonable agreements have been reached. Three different regimes are identified based on the captured images. The jet velocity plays less significant role in the low heat flux cases for the saturated jets, but more in the high heat flux scenarios for the subcooled jet impingement boiling. The latent heat of phase change weakens the effect of jet velocity when crossing the boiling point. Moreover, a higher velocity of the saturated jet results in a later transition to the fully established boiling regime with a higher wall superheat. After the transition point, the predicted wall heat flux components are almost independent of wall heat flux or wall superheat, indicating that they are the good indicators to determine the boiling regime in the simulation.